Comparison of the Bilateral Deficit in Muscular Power of Soccer Players and Students - Cofre-Bolados, C; Herrera-Valenzuela, T (UNIV CORUNA, SERVICIO PUBLICACIONS, 2018)
Introduction: The bilateral deficit (BLD) corresponds to the decrease in bilateral muscular actions strength compared to the addition of unilateral actions. Know the BLD could help assess the neuromuscular capacity of athletes. Objective: To compare the BLD in jump height and power of inferior members between professional soccer players and university students. Method: counter movement jump and use of arm Abalakov (ABK) type were evaluated in unipodal and bipodal mode, obtaining the maximum height jumped and the estimated power, to determine BLD. Results: Bilateral jump height of 38.6 cm and unilateral right-to-left were observed in students respectively 20,6 -20,9 cm (BLD -7,8%). In soccer players there is no BDL (5,6%) with a bilateral jump height of 39,1 cm and unilateral of 17,8-19,2 cm, with a difference between groups (p<0,05). For power, BLD was observed in both groups, students -45,5% with a bilateral power of 3.430 watts and unilateral of 2.496 and 2.514 watts. The players presented BLD -37,7% with a bilateral power of 3.431watts and unilateral of 2.388 and 2.400 watts. There were differences between both groups (p<0,05). Conclusion: professional soccer players do not present bilateral deficit in jump height and present lower bilateral deficit in estimated power in comparison to university students.